Persistent Pulmonary Interstitial Emphysema With Respiratory Infection: A Clinicopathological Analysis of Six Cases and Detection of Infectious Pathogens by Metagenomic Next-Generation Sequencing (mNGS) - Zhou, Ping; Wang, Weiya; Fu, Yiyun; Zhang, Ying; Liang, Zuoyu; Tang, Yuan; Jiang, Lili (Frontiers in Pediatrics, 2022)
Background: Persistent pulmonary interstitial emphysema (PPIE) is known to be related to mechanical ventilation and preterm. However, PPIE has also been reported rarely in nonventilated infants and full-term infants. Its relationship with respiratory infection has rarely been reported in the literature. PPIE is difficult to diagnosis, always mimics with other congenital thoracic malformations (CTMs), such as congenital cystic adenomatoid malformation (CCAM). Objective: The objective of this study was to evaluate clinicopathological and radiographic features of PPIE with respiratory infection and to detect the possible infectious pathogens. Methods: From January 2011 to December 2019, six cases confirmed pathologically with PPIE from a large cohort of 477 resected CTMs in West China Hospital of Sichuan University. Clinical and radiographic features were obtained from patients' medical records and follow-up. The present study aimed to analyze clinicopathological and radiographic features and to detect the infectious pathogens by metagenomic next-generation sequencing (mNGS). Results: Six PPIEs included four girls and two boys, ranged from 2 months to 5 years. 100% (5/5) available cases were full-term and without mechanical ventilation. CCAM were suspected in 66.7% (4/6) patients. 66.7% (4/6) cases affected a single lobe, and 33.3% (2/6) cases affected both lung lobes. Clinically, all six PPIEs were presented with symptom of respiratory infection, and diagnosed with pneumonia. All six patients were treated by surgery after anti-infective treatment. The pathologic characteristics showed lung cysts with variable size along the bronchovaslcular bundles, the cysts had a discontinuous fibrotic wall with a smooth inner surface, lined with uninucleated and/or multinucleated macrophages. Streptococcus pneumoniae was detected in patient No.1. Human beta-herpesvirus 5 was detected in patient No.2. Neisseria mucosa, Neisseria sicca, Prevotella melaninogenica, and Prevotella histicola and Fusobacterium nucleatum were detected in patient No.5, and no infectious pathogen was detected in 50% (3/6, No.3, No.4 and No.6) cases. Conclusion: Six rare cases of PPIE with respiratory infection were treated by surgery after anti-infective treatment. All available five cases were full-term infants without mechanical ventilation. The histological characteristics of PPIE were the wall of cysts composed of a thin layer of discontinuous fibrous tissue and lined with uninucleated or/and multinucleated macrophages.